Fluoroscopic Evaluation of the Bile Ducts: Anatomic Variants, Benign and Malignant Pathologies and Bile Leaks: Part II. (15th May 2021) - Sridhar, Shravan; Keshav, Nandan; Shiehmorteza, Masoud; Thompson, William M.
Abstract : In the first installment in this series (volume 44, number 9), the normal anatomy and anatomic variants of the bile ducts were discussed. The techniques of direct cholangiography (DC) and how to interpret DC were reviewed. Finally, the nonstrictured bile duct abnormalities were covered. In this article, the strictured bile duct abnormalities and bile leaks will be thoroughly discussed to conclude the series.